PSIKOEDUKASI “KENALI DIRI” UNTUK MENINGKATKAN PEMAHAMAN REMAJA TENTANG PERBANDINGAN SOSIAL - Septianto, Ahmad Nur; Hanurawan, Fattah; Khaerunniswa, Adzkiya; Mustikawati, Evi (Universitas Islam Indonesia, 2025)
ABSTRACT: Social comparison among adolescents in the digital era has the potential to affect their psychological well-being. This study aims to test the effectiveness of a single-session psychoeducation session “Kenali Diri” in improving adolescents’ understanding of social comparison. The study used a quasi-experimental one-group pretest–posttest design involving 49 eleventh-grade students at a senior high school in Malang City, selected through cluster random sampling. The research instrument consisted of 10 cognitive questions based on levels C1-C2 of Bloom’s Taxonomy. Data were analyzed using a paired samples t-test after meeting the normality assumption as indicated by the Shapiro–Wilk with p = .106 (p > .05). The results demonstrated an increase in students’ cognitive understanding scores after participating in psychoeducation (p < .001) with a moderate effect strength (d = .55). Brief school-based psychoeducation is effective in improving adolescents’ basic psychological literacy related to social comparison. Further programs are recommended to be developed sustainably, enriched with practical components to support adolescent mental health in the school environment. Key words: Adolescent, psychoeducation, social comparison, student. ABSTRAK: Kecenderungan perbandingan sosial di kalangan remaja di era digital berpotensi memengaruhi kesejahteraan psikologis mereka. Penelitian ini bertujuan untuk menguji efektivitas psikoedukasi satu sesi “Kenali Diri” dalam meningkatkan pemahaman remaja mengenai perbandingan sosial. Penelitian menggunakan desain kuasi-eksperimen one-group pretest–posttest design dengan melibatkan 49 siswa kelas XI di salah satu SMA Negeri di Kota Malang yang dipilih melalui cluster random sampling. Instrumen penelitian berupa 10 soal kognitif disusun berdasarkan Taksonomi Bloom pada level C1–C2. Data dianalisis menggunakan paired samples t-test setelah memenuhi asumsi normalitas berdasarkan uji Shapiro–Wilk dengan nilai p = .106 (p > .05). Hasil analisis menunjukkan peningkatan skor pemahaman kognitif siswa setelah mengikuti psikoedukasi (p < .001) dengan kekuatan efek moderat (d = .55). Psikoedukasi singkat berbasis sekolah efektif sebagai sarana peningkatan literasi psikologis dasar remaja terkait perbandingan sosial. Program psikoedukasi selanjutnya disarankan untuk dikembangkan secara berkelanjutan dan diperkaya dengan komponen praktis guna mendukung kesehatan mental remaja di lingkungan sekolah. Kata kunci: Perbandingan sosial, psikoedukasi, remaja, siswa.